PENGARUH EARNINGS, RESIDUAL INCOME, ECONOMIC VALUE ADDED DAN OPERATION CASH FLOW TERHADAP RETURN SAHAM - Mardani, Ronny Malavia (Fakultas Ekonomi, UIN Maliki Malang, 2013)
This study intends to test of: first, the effect of earnings, residual income, economic value added, and Operation Cash Flow simultaneously on returns received by shareholders manufacturing companies listed on the Indonesia Stock Exchange and second the effect of earnings, residual income, economic value added, and Operation Cash Flow partially on returns received by shareholders manufacturing companies listed on the Indonesia Stock Exchange. This study uses linear regression to see the contribution of each independent variable in influencing stock returns. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2008-2011. Being sampled in this study was determined using purposive sampling method. With purposive sampling method found 40 companies that meet the criteria and deserves to be sampled. Based on the analysis it can be concluded simultaneously Earnings, Economic Value Added, Residual Income and Cash Flow Operation significant effect on the return. In partially, only Earnings and Cash Flow Operation significant effect on the return.